Influence of soil physicochemical properties on diversity and distribution of aquatic vegetation in the riverine forested habitats - Mina Javed; Muhammad Sajid Aqeel Ahmad; Wasifa Rani; Mansoor Hameed; Farooq Ahmad (International Journal of Applied and Experimental Biology)
Riverine flora is one of the most dynamic aspects of a landscape, and it involves species which are adapted and specialised to grow in a range of environmental conditions. An ecological analysis was conducted to describe the phyto-sociological and floristic structure of the plant species in the riverine forest at Balloki along moisture gradients caused by river bank. A random quadrat method with a quadrat size of 1 × 1 m was used for sampling of the riverine site. All plant species growing in the riverine habitats were collected and identified. A detailed survey was conducted to record the ecological attributes such as density, frequency, cover, and importance value. These values were then used to calculate the relative values of these ecological indicators. These ecological indicators were correlated with various soil physical parameters (soil texture, moisture contents and saturation percentage), chemical properties (ECe and pH), and nutrients (Na, Ca, K and N). Most of the species were linked to sites 3 and 4 with high moisture content, low ECe, acidic pH and moderate nutrient composition. The species with the highest ecological importance were Cynodon dactylon, Rumex dentatus and Saccharum spontaneum which accounted for more than 80% of the total abundance. It was concluded that species distribution differed significantly along the four study sites mainly depending on the soil-physicochemical features of the study sites.